Odpowiedź :
[tex]\frac{6}{\frac{3}{4} } =6*\frac{4}{3} =2*4=8\\\\\frac{\frac{1}{2} }{2}= \frac{1}{2} *\frac{1}{2} =\frac{1}{4} \\\\\frac{\frac{2}{3} }{\frac{3}{2} } =\frac{2}{3} *\frac{2}{3} =\frac{4}{9} \\\\\frac{\frac{2}{3} }{\frac{2}{5}}=\frac{2}{3} *\frac{5}{2} =\frac{5}{3}\\\\\frac{\frac{4}{5} }{10} =\frac{4}{5} *\frac{1}{10} =\frac{2}{25} \\\\2*\frac{4}{\frac{1}{2} } =2*4*2=16\\\\\frac{\frac{3}{4} }{5} :2=\frac{3}{4} *\frac{1}{5} :2=\frac{3}{20} *\frac{1}{2} =\frac{3}{40} \\\\[/tex]
[tex]2:\frac{6}{\frac{4}{3} } =2*\frac{\frac{4}{3}} {6} =\frac{4}{3} *\frac{1}{3} =\frac{4}{12} =\frac{1}{3}[/tex]